A Resemblance to Peritoneal Carcinomatosis – Abdominal Tuberculosis - Wismayer, Richard (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Introduction: Tuberculosis remains a global public health concern. Abdominal tuberculosis is an atypical presentation and since it is extrapulmonary it may delay the diagnosis and treatment of this condition. The mortality associated with treated abdominal tuberculosis is 15% despite being a treatable disease. The objectives of this case report was to discuss a typical presentation of abdominal tuberculosis and highlight the difficulties which are encountered in the diagnosis of abdominal tuberculosis. Presentation of Case: A 56 year old gentleman admitted to hospital with a 1 week history of generalised abdominal pain associated with abdominal distention and vomiting. The chest-X-ray was unremarkable and the abdominal X-ray revealed air-fluid levels. Laboratory investigations revealed a high white cell count at 14,000µl. At laparotomy, multiple small whitish deposits in the greater omentum and on the bowel with a frozen abdomen was found. Biopsy of these whitish deposits showed histology of giant Langhans multinucleated cells with acid-fast bacilli and necrosis and a granulomatous inflammatory process. Anti-tuberculosis treatment was initiated using a combination of antibiotics and he made an uneventful recovery. Discussion: The clinical abdominal TB presentations include acute, subacute or chronic disease. The chest-X-ray of our patient showed no evidence of pulmonary tuberculosis however this is not surprising as less than half of patients with abdominal TB have pulmonary tuberculosis. Ultrasound findings in abdominal TB include thickening of the wall of the ileum, caecum and colon and associated ascites. When malignancy cannot be ruled out with certainty then laparotomy is recommended with biopsy of any peritoneal lesions, omental lesions and a lymph node biopsy. Conclusions: Judicious use of diagnostic procedures and a high index of suspicion may help in the timely diagnosis and treatment of abdominal tuberculosis. Biopsy of peritoneal/omental lesions and of a mesneteric lymph node is advisable to distinguish abdominal tuberculosis from peritoneal carcinomatosis.